COMPARISONAL ANALYSIS OF FINANCIAL RATIO BEFORE AND DURING THE COVID-19 PANDEMIC OF GO PUBLIC MANUFACTURING COMPANIES LISTED ON IDX - Sri Yaumi; Tri Winarsih; Bayu Malikhul Askhar; Abdul Majid (Universitas Islam Lamongan, 2022)
This study aims to analyze the comparison of financial ratios before and during the covid-19 pandemic. The samples of this study were 21 go public manufacturing companies listed on the IDX. The data taken in this study were the 2nd ,3rd and 4th quarters of 2019 and the 2nd,3rd and 4th quarters of 2020. The analytical technique used in this study was Paired-Sample T-test. The results of the study indicated that liquidity was different before and during the covid-19 pandemic, while profitability, solvency, dividend policy and firm value were just the same as before and during the pandemic. This research indicated that manufacturing companies were still able to survive due to the Covid-19 pandemic. If the pandemic lasts longer, it is hoped that the company will maintain company value in order to survive and gain the trust of investors by using certain strategies. Because of this COVID-19 pandemic, the potential investors are more selective in choosing companies to invest.